PERAN ORANG TUA DALAM PENGGUNAAN TEKNOLOGI PADA PEMBELAJARAN ONLINE TINGKAT SD DI MASA PANDEMI COVID-19 - Unik Hanifah Salsabila; Rachmad Sukriyanto; Erik Purwanti; Purwaningsih Purwaningsih; Muhammad Iqbal Aldi Satria (Jurnal Inovasi Penelitian, 2021)
This study aims to determine the learning effectiveness of elementary school students during the Covid-19 pandemic or what is often called online learning, which is indirect face-to-face learning between teachers and students as usual, but only through virtual (screens cell phone or laptop). Where during a pandemic everyone must carry out all their activities from home, including elementary school students. Research through interviews throughmedia WhatsApp with the guardians of the students gave responses about the various obstacles in this online learning. And parents with all kinds of efforts to continue to seek education in any circumstances for their children, including when Indonesia is being hit by the Covid-19 pandemic. Online learning is the choice of academics from various walks of life from kindergarten to college. This was chosen because it was considered the most effective and efficient enough, both for the students and their guardians and for the teachers. For the smooth running of this online learning, the main thing that must be considered and prepared is a cell phone or laptop complete with the contents of a quota or data package, also a place that can be reached by the network, and what is no less important is the assistance of parents in operating the tool while the child is learning or do the work of the teacher. These facilities are used to exchange information from two directions for the sake of supporting education. This situation forces all parents, students and teachers to really maximize technology so that learning objectives can be achieved properly, children's achievement does not decline even though they do it remotely.